2019
DOI: 10.1103/physrevapplied.11.064038
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Mode Coupling and Coherence in a Spin Hall Nano-Oscillator with Perpendicular Magnetic Anisotropy

Abstract: We experimentally study the dynamical modes excited by spin current in Spin Hall nano-oscillators based on the Pt/[Co/Ni] multilayers with perpendicular magnetic anisotropy. Both propagating spin wave and localized solitonic modes of the oscillation are achieved and controlled by varying the applied magnetic field and current. At room temperature, the generation linewidth broadening associated with mode hopping was observed at currents close to the transition between different modes and in the mode coexistence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Prior experimental and theoretical studies have shown that the bullet mode emerges from the linear spectrum of spin-waves above a critical current determined by damping, without any energy barrier for its formation [13,14,19]. In contrast, the droplet mode involves an inverted static core, whose nucleation is associated with a certain energy barrier.…”
Section: B Spectral Characteristics Of Vnc-shno At 60 Kmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior experimental and theoretical studies have shown that the bullet mode emerges from the linear spectrum of spin-waves above a critical current determined by damping, without any energy barrier for its formation [13,14,19]. In contrast, the droplet mode involves an inverted static core, whose nucleation is associated with a certain energy barrier.…”
Section: B Spectral Characteristics Of Vnc-shno At 60 Kmentioning
confidence: 99%
“…In contrast to the droplet, the bullet mode is characterized by large-amplitude precession of the central region, with the spatial characteristics determined by a combination of exchange stiffness, nonlinearity, and spin torque [27]. This mode is commonly observed in SHNOs and the conventional multilayer STNOs with in-plane magnetic anisotropy, or PMA free layer at sufficiently large inplane fields [13,15,19,36]. The magnetic droplet mode is generally expected to exhibit larger spectral intensities than the bullet mode, due to the large precession angle of magnetization in the dynamical domain wall.…”
Section: Device Fabrication and Electronic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spin Hall nano-oscillators (SHNOs) are a class of miniaturized, ultra-broadband, microwave signal generators [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] where the spin Hall effect [21][22][23] converts a direct charge current into a transverse pure spin current, transferring angular momentum [24][25][26] into a nearby ferromagnetic layer, resulting in current and magnetic field tunable spin wave (SW) autooscillations (AOs); a microwave voltage is then generated via the anisotropic magnetoresistance of the magnetic layer. Thanks to their simple bilayer structure, nano-constriction SHNOs offer a number of advantages such as straightforward fabrication processes, flexibility in material choices, significant freedom in layout, and direct optical access to the active auto-oscillating region, which makes them attractive for fundamental studies of highly nonlinear and interacting SWs.…”
mentioning
confidence: 99%